The impact of Danmu technological features on consumer loyalty intention toward recommendation vlogs: a perspective from social presence and immersion - Yang, Tiantian; Yang, Feng; Men, Jinqi (Information technology & people (West Linn, Or.), 2022)
PurposeThis study investigates how Danmu (danmaku) technological features (DTFs) of recommendation vlogs (rec-vlogs) impact consumer experiences and decisions.Design/methodology/approachThe authors adopt the partial least squares structural equation modeling (PLS-SEM) technique with a sample of 422 viewers of Danmu-enabled rec-vlogs to examine the proposed model.FindingsThe DTFs positively affect consumer loyalty intentions through the mediation of social presence and immersion. Also, vlogger-product congruency significantly moderates the relationship between social presence and immersion.Originality/valueWith the increasing popularity of vlogs, retailers have adopted the vlog as a new marketing channel to connect with consumers. Although a growing body of studies focuses on this phenomenon, little is known about how DTFs help to increase consumer loyalty toward using rec-vlogs as product information sources. Anchored on the stimulus–organism–response framework, this study investigates how pseudo-synchronicity, Danmu-content congruency and parallelism, three DTFs used in rec-vlogs, impact consumer experiences of social presence and immersion, eventually influence the consumers' loyalty intentions toward rec-vlogs. The authors also examine whether the effect of social presence on immersion is contingent on vlogger-product congruency. These findings have implications for both researchers and practitioners to understand the effect of DTFs in the context of rec-vlogs.